Exploring Sustainable Initiatives for Campus Operations at the University of Technology Sarawak - Nurzalikha Sa’adi; Faisal Tamrulan; Nur Fasihah Ngah Seron; Maximus Balla Tang; Asmah Alia Mohamad Bohari (Online Journal for TVET Practitioners, 2025)
Sustainable initiatives are crucial for addressing environmental challenges and promoting development. Sustainability is becoming a top priority for educational institutions worldwide, with the higher education sector constantly striving to incorporate environmentally friendly practices into its operations. However, more information about the current sustainable initiatives at the University of Technology Sarawak (UTS) is required. Hence, this research aims to investigate UTS's sustainability initiatives, focusing on campus operations. This research adopted a qualitative approach to investigate sustainable initiatives at the University of Technology Sarawak (UTS). Using a case study method, the study provided an in-depth analysis of sustainable practices across the campus's physical and built environments. Data were collected through campus site inventories from the Maintenance Facilities and Security Department, UTS, and site analyses, which documented and evaluated various operational aspects. The findings identified eight critical areas for achieving sustainable campus operations: buildings, air and climate, energy, food, grounds, transportation, waste management, and water sustainability. The sustainability initiatives implemented by UTS have successfully mitigated its adverse environmental effects and fostered a widespread culture of sustainability across the institution. These notable discoveries have generated a surge of interest from other higher education institutions, motivating them to contemplate and adopt equally extensive, campus-wide strategies that may significantly enhance their sustainability endeavors.